COVID-19 in B Cell-Depleted Patients After Rituximab: A Diagnostic and Therapeutic Challenge - Furlan, Anna; Forner, Gabriella; Cipriani, Ludovica; Vian, Elisa; Rigoli, Roberto; Gherlinzoni, Filippo; Scotton, Piergiorgio (Frontiers in Immunology, 2021)
B cell-targeting strategies such as rituximab are widely used in B cell hematologic malignancies, rheumatologic and musculoskeletal diseases and a variety of autoimmune disorders. The purpose of this paper is to illustrate how exposure to anti-CD20 treatment profoundly affects B cell functions involved in anti-SARS-CoV-2 immunity and significantly impacts on the clinical and serological course of SARS-CoV-2 infection, long term immunity and vaccine responses. The data presented here suggest that the effects of B cell-depleting agents on adaptive immunity should be taken into account for the proper selection and interpretation of SARS-CoV-2 diagnostics and to guide appropriate therapeutic approaches and protective measures. Combination therapeutic strategies including immunotherapy in association with prolonged antiviral treatment may play a decisive role in the setting of B cell immune deficiencies.